Optimalisasi Penggunaan Media Sosial sebagai Implementasi Strategi Peningkatan Penjualan pada UMKM Koremin - Anief, Raifa Praharsa; Putri, Amalia; Kusumah, Dwi Jaya; Khitmatyar, Ridha Faatihah; Widyaningsih, Aristanti (Universitas Nusantara PGRI Kediri, 2024)
The existence of social media has become embedded in people's lives in the digital era. Not only for communicating, currently many business people use social media Instagram, Tiktok, Twitter and Facebook to promote their businesses. Koremin MSMEs, in running their business, also have social media accounts which are used as marketing media. However, the use of social media needs to be accompanied by creativity and the creation of promotional content that is in line with existing trends so that it can reach a wider range of consumers. The service is carried out in order to help MSMEs be able to use their social media optimally to achieve sales targets. The implementation method is observation, interviews and mentoring for three months. The research results show that Koremin MSMEs are able to use their social media optimally and achieve the expected targets.